True transition to practice: a role-reversal simulation - Preti, Beatrice; Sanatani, Michael (Canadian Medical Education Journal, 2023)
Implication Statement This article explores a direct-observation simulation swapping resident and consultant roles as a measure to assess competence during the final “transition to practice” phase of residency. As indicated by the Royal College, assessment of competency in this stage should include direct observation; however, this is challenging to implement, both from the perspective of a busy clinical environment, but also logistically, as a final-stage resident is still a learner in a consultant clinic. Our suggested approach allows for both real-world experience for the resident as well as direct observation and assessment by the consultant, thus providing the resident with targeted, actionable feedback, as well as ensuring the final-stage resident is competent for practice.